Rancang Bangun Game Adventure Gyro Berbasis Android Menggunakan Model Rational Unified Process (RUP) - Edy Santoso; Sulistyowati Sulistyowati; Andy Rachman (INTEGER: Journal of Information Technology, 2016)
People nowadays mostly use mobile device for their daily needs such as for playing game, Smartphone with android OS because they can play it anywhere. The game of Adventure Gyro was about the adventure of a child to save animal. The writer intended to make game as entertainment media because this contained message to save animal in our surroundings using rational unified process (RUP) model that consist of some phases such as; inception, elaboration, construction, transition. The early design of game was made in first phase, inception. The further design of game plot was conduction in elaboration phase. Then, game was made for sure in construction phase. The next was transition phase to test the game. After test conducted, the questionnaire on adventure gyro was given to 30 users who tried this game. From the result, it was found that the usability of this game was 85%, information quality was 79%, and interaction quality was 75%. Therefore, it can be concluded that this game is proper to be used.